الحماية القانونية لبطاقة الإئتمان - باشي لمياء; سباق عبد القادر حليمة; عليان مروة (جامعة الوادي, 2024)
وقد أدخلت المؤسسات التي تصدر هذه البطاقة الائتمانية، بما في ذلك المؤسسات الفرنسية، العديد من التعديلات على متن البطاقة، ولا تزال هذه التعديلات تحدث حتى يومنا هذا من أجل توفير حماية فعالة لكل من الحائز والتاجر وحتى للطرف المصدر. التعامل مع نظام الدفع الإلكتروني، الذي يتجسد من خلال مختلف أساليب الدفع الإلكترونية، بما في ذلك بطاقات الائتمان من مختلف الأنواع، يقتضي ضرورة التقيد بالشروط التي تفرضها السلطات التي تصدر هذه الأدوات، ومن بين هذه الالتزامات الاستخدام المشروع لهذه الأداة، فضلا عن ضرورة حمايتها من الضياع أو السرقة، ومن الضروري أيضا أخذ زمام المبادرة. بإخطار وفي الوقت المطلوب قانوناً من الحائز القانوني إذا فقدت البطاقة أو سرقت منه، وبالتالي، إذا استعملها طرف ثالث وجد هذه البطاقة المفقودة أو سرقها من مالكها الحقيقي في عمليات سحب أو مدفوعات غير قانونية، هنا تنشأ المسؤولية الجنائية. مواجهة الآخرين نتيجة انتهاك الأخير لبطاقة الائتمان. The institutions that issue this credit card, including the French institutions, have introduced many modifications to the body of the card, and these modifications are still occurring to this day in order to provide effective protection for both the holder and the merchant and even for the issuing party. Dealing with the electronic payment system, which is embodied through various electronic payment methods, including credit cards of various types, requires the necessity of adhering to the terms imposed by the authorities issuing these tools, and among these obligations is the legitimate use of this tool, as well as the necessity of protecting it from loss or theft, and it is also necessary to take the initiative. By notification and at the time legally required by the legal holder if the card is lost or stolen from him, and accordingly, if a third party who finds this lost card or steals it from its real owner then uses it in illegal withdrawals or payments, here the criminal liability arises. Confronting others as a result of the latter’s infringement on the credit card.
،البطاقات الائتمان، المؤسسات،